2013
DOI: 10.5142/jgr.2013.37.425
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-processed Korean Red Ginseng extracts protects against skin damage induced by UVB irradiation in hairless mice

Abstract: UV irradiation is the main factor contributing to skin damages that are associated with an excessive production of matrix-degrading metalloproteinase (MMP)-1 and a deficient expression of collagens. To date, red ginseng has been revealed to possess many biomedical effects, such as anti-aging, anti-oxidation, and anti-inflammatory. In this study, we prepared the Korean Red Ginseng extracts treated with enzyme (KRGE) and investigated the effects of dietary KRGE on the formation of wrinkles generated by UVB irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…36 In an in vivo study of human skin, chronic UVB exposure was found to decrease the production of procollagen type I, leading to collagen loss and increased wrinkling, skin thickening, and reduced skin elasticity. 28,37 Using histological techniques, we observed the changes associated with photoaging in hairless mice treated with CSE. Specifically, mice treated with CSE had thinner epidermal layers and denser collagen fibers compared with untreated mice (Fig.…”
Section: Figmentioning
confidence: 99%
“…36 In an in vivo study of human skin, chronic UVB exposure was found to decrease the production of procollagen type I, leading to collagen loss and increased wrinkling, skin thickening, and reduced skin elasticity. 28,37 Using histological techniques, we observed the changes associated with photoaging in hairless mice treated with CSE. Specifically, mice treated with CSE had thinner epidermal layers and denser collagen fibers compared with untreated mice (Fig.…”
Section: Figmentioning
confidence: 99%
“…However, the overall change in R4 was greater in the EG-treated group than in the 2 placebo group (Table 6). EG treatment decreased the arithmetic roughness average (R5) 3 value (down to 0.01±0.01 A.U. ), whereas placebo did not (Table 7).…”
mentioning
confidence: 81%
“…10 2 Global photodamage scores of eye wrinkles were diminished by treatment with EG. 3 Crow's feet wrinkles in the EG treatment group appeared thinner and dimmer in photographs 4 compared with placebo. These results suggest that topical application of EG may have anti-5 wrinkle effects.…”
mentioning
confidence: 94%
See 2 more Smart Citations